Decision theory as philosophy - Kaplan, Mark (Cambridge Univ. Press, 1996)
It has been over sixty years since Ramsey first argued for the significance of decision theory to epistemology. Yet many philosophers remain unconvinced. The familiar probabilistic constraints decision theory imposes on opinion and confirmation seem too demanding, too prudential in nature and too tangential to our concern with the propriety of categorical belief and knowledge. How important are these concerns? Mark Kaplan argues that they are very important - but that a properly modified and interpreted Bayesian decision theory can meet them. His brief is that, suitably formulated, Bayesian decision theory is of the most profound philosophical consequence to the way we are accustomed to think about inquiry, criticism and rational belief. Kaplan makes his case in a clear and compelling way, and with a minimum of technical detail. The modest variant of Bayesian decision theory to which he appeals is new, well-motivated and easy to follow. Most proofs are relegated to an appendix. A brief primer on probability is also provided. This book is not just an original contribution to Bayesian epistemology. It is also the most accessible treatment available of the relation Bayesian epistemology bears to the rest of the field.